2014
DOI: 10.1353/hpu.2014.0154
|View full text |Cite
|
Sign up to set email alerts
|

Women as Health Care Decision-Makers: Implications for Health Care Coverage in the United States

Abstract: Women in the United States make approximately 80% of the health care decisions for their families, yet often go without health care coverage themselves. The implementation of the Affordable Care Act provides an historical opportunity for women to gain health care coverage for themselves and their families. The focus of this commentary is on women's leadership roles in the context of health care decision- making and Affordable Care Act education and outreach, and implications for reaching broader health and soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 7 publications
4
40
0
Order By: Relevance
“…Of the more than 50% expressing interest in an online information sharing portal for CAM, women and younger participants expressed greater interest. The role of women in information-seeking and health care decision making for family members is well documented [ 14 , 15 ]. The phone interviews documented similar behaviors amongst women and men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the more than 50% expressing interest in an online information sharing portal for CAM, women and younger participants expressed greater interest. The role of women in information-seeking and health care decision making for family members is well documented [ 14 , 15 ]. The phone interviews documented similar behaviors amongst women and men.…”
Section: Discussionmentioning
confidence: 99%
“…The main source for CAM information was anecdotal through family and friends, with female family members playing a major role in steering male family members toward CAM use. This is not surprising, as studies have shown that women make up to 80% of the health care decisions for their families in the United States [ 14 ]. A Canadian study suggested that in many cases, patients would prefer to receive CAM information from trusted resources, such as their oncologists, but physicians were often not equipped to provide the necessary information [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The LSP-MHL studies and other research with parents confirm that mothers remain the primary caregivers of children, and the primary managers of health and healthcare at home [15]. It is likely that fathers have MHL and perhaps other distinctly paternal health literacy skills; but available data on fathers is insufficient to assess those skills or their impacts.…”
Section: Health Disparities Begin Before Birth -Mothers In Povertymentioning
confidence: 98%
“…Our recruitment efforts uncovered much more interest from women, and specifically from mothers. Since mothers are more often primary decision makers for children's health care, 37 we believe our results results reflect children's experience in the health care setting. In addition, our qualitative sample included more stakeholders from urban areas of the state.…”
Section: Discussionmentioning
confidence: 64%